(untitled) (Philosophy and Progress, 2022)
This study examines the role of the principle of Sikh liberalism in promoting communal harmony in today’s world. Communal harmony has been under threat in almost all countries for decades, and bigotry, distrust, and animosity prevail among the followers of diverse faithbased communities. Individuals need to be whole-hearted, liberal in approach, and tolerant toward the followers of other communities to reduce such inconsistencies in our society. The paper explores that the ideology of Sikh liberalism can be a role model for establishing peace in today’s world of communal violence. This work is a sincere effort to deal with several issues, e.g., humanism, tolerance, fraternity, equality, freedom, secularism, religious pluralism, and accessibility to and honor for contrasting opinions, based on the principle of Sikh liberalism, which are the root of Sikh liberalism. The qualitative research evaluates the all-embracing aspects of Sikhism, where the liberal notion of Guru Granth Sahib and the liberal attitudes of the Sikh Gurus, especially Guru Nanak (1469-1539), the founder of Sikhism, have mainly been highlighted. It discovers the role of Sikhism in promoting communal harmony by analyzing the idea of Sikh liberalism. Thus, the study aims to make the states, governments, and the general people aware of their responsibilities and duties towards promoting communal harmony through comprehending the Sikh approaches to liberalism. Philosophy and Progress, Vol#69-70; No#1-2; Jan-Dec 2021 P 189-209